Refletindo as recentes catástrofes ambientais em território nacional: uma visão dos professores do curso de Ciências Biológicas da UFSCar de São Carlos - Constantino, André Luis (Universidade Federal de São Carlos, 2022)
In this work we aim to understand how higher education teachers interpret recent Brazilian environmental catastrophes. Three professors from the Biological Sciences Degree at UFSCar in São Carlos responded to a virtual questionnaire, and the responses were analyzed qualitatively. All teachers declared to be aware of the recent national environmental disasters, Mariana, Brumadinho and oil spill. They demonstrated very pertinent understandings regarding environmental catastrophes, considering their complexity and need for critical analysis, although on some occasions there are controversies regarding these phenomena and also the role of the media in communication. Despite the many ills and the destructive relationship between human beings and the environment, the teachers pointed out the need to look at this with perspectives of change and transformation towards a better society that is based on other types of socio-environmental values ​​and practices – something which can guide research and practices related to this topic. This includes the need for conceptual precision when approaching such themes, searching for terms that can represent the intentionality and necessary accountability for environmental events. We believe that environmental education is extremely important in training people committed to the sustainability of humanity in its relationship with the environment, and understanding current scientific and technological development is fundamental to establishing more accurate diagnoses and proposing different horizons. We point to the idea of ​​risk society as a great enhancer for Environmental Education and critical training in general.
Reflecting the recent environmental catastrophes in the national territory: a view from professors of the Biological Sciences course at UFSCar in São Carlos
Keywords: Educação ambiental; Catástrofes ambientais; Visão de professores; Environmental education; Environmental catastrophes; Teachers’ view; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO